Linagliptin: farmacology, efficacy and safety in type 2 diabetes treatment - Guedes, Erika Paniago (BioMed Central, 2013)
Type 2 diabetes mellitus (T2DM) has a high prevalence and incidence around the world. The complex pathophysiology mechanism is among the barriers for diabetes treatment. Type 2 diabetes patients have dysfunction in incretin hormones (as glucagon-like peptide-1 or GLP-1, and glucose-dependent insulinotropic polypeptide or GIP). By inhibiting the dipeptidyl peptidase-4 (DPP-4) enzyme, it is possible to slow the inactivation of GLP-1 and GIP, promoting blood glucose level reduction in a glucose-dependent manner. Linagliptin is a highly specific and potent inhibitor of DPP-4 that is currently indicated for the treatment of type 2 diabetes. Clinical studies with linagliptin demonstrated efficacy in reducing glycated hemoglobin (HbA1c) levels in type 2 diabetes patients, while maintaining a placebo-like safety and tolerability profile. Linagliptin has an interesting pharmacokinetic profile in terms of its predominantly non-renal elimination and the main implication of this characteristic is that no dose adjustment is necessary in patients with renal disease. Also, no dose adjustment is required in patients with hepatic insufficiency, as well in elderly or obese patients. This article will review the pharmacokinetic profile, efficacy data and safety aspects of linagliptin in type 2 diabetes patients.